2010
DOI: 10.1002/chem.201001648
|View full text |Cite
|
Sign up to set email alerts
|

On the Trimerization of Cyanoacetylene: Mechanism of Formation of Tricyanobenzene Isomers and Laboratory Detection of Their Radio Spectra

Abstract: In support of a deeper understanding of the chemistry of cyanoacetylene--a known constituent of planetary atmospheres and interstellar space--theoretical and experimental studies address the chemical mechanism of dimerization and trimerization, and provide high-resolution rotational spectra of two of the trimeric products, 1,2,3- and 1,2,4-tricyanobenzene. Analysis of the rotational spectra is particularly challenging because of quadrupolar coupling from three (14)N nuclei. The laboratory rotational spectra pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In 1993, Hopf and Witulski reported that 1,2,4- and 1,2,3-tricyanobenzenes were formed with other products when cyanoacetylene was heated at 160 °C in a sealed tube . Recently, they gave the energies of the products and the proposed intermediates, but no information about the transition states was given …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1993, Hopf and Witulski reported that 1,2,4- and 1,2,3-tricyanobenzenes were formed with other products when cyanoacetylene was heated at 160 °C in a sealed tube . Recently, they gave the energies of the products and the proposed intermediates, but no information about the transition states was given …”
Section: Introductionmentioning
confidence: 99%
“…The interesting phenomena of these uncatalyzed thermal cyclotrimerizations of alkynes have attracted some attention. , However, several questions remain unanswered because of the scarce experimental and computational evidence. Why can these alkyne cyclotrimerization reactions occur under thermal reaction conditions?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of cytosine from urea and cyanoacetaldehyde was also examined . Cyanoaldehyde may be a product of the hydrolysis of cyanoacetylene, which, in turn, is a derivative of acetylene , (cyanoacetylene can be produced by spark discharge in a CH 4 /N 2 mixture). , Moreover, purine bases can be the product of the reaction of cyanoacetylene with cyanamide through barrierless cyclization through a small number of stages …”
Section: Acetylene In Prebiotic Chemistry Evolutionmentioning
confidence: 99%
“…So far, the 14 N nuclear quadrupole coupling of nitrile groups were mainly interpreted for planar molecules like tricyanobenzenes and substituted cyanobenzenes. In those molecules, the CN bond is always expected to be polarized due to the difference in electronegativity of the two elements [124,125], while the mesomeric character changes by interactions with the aromatic system to which they are bound. For acetone cyanhydrin, we assume that the electronic withdrawal is mainly reflected in ionic rather than mesomeric changes of the CN bond.…”
Section: N Nuclear Quadrupole Couplingmentioning
confidence: 99%